Comparison of Postoperative Outcomes Between Percutaneous Endoscopic Lumbar Interbody Fusion and Minimally Invasive Transforaminal Lumbar Interbody Fusion for Lumbar Spinal Stenosis - Lin, Lu; Liu, Xiao-Qin; Shi, Lei; Cheng, Si; Wang, Zhi-Qiang; Ge, Qi-Jun; Gao, Ding-Zhi; Ismail, Amadou Cheffou; Ke, Zhen-Yong; Chu, Lei (Frontiers in Surgery, 2022)
Objective: This study aimed to compare postoperative outcomes in surgical and patient-reported outcomes (PROs) between percutaneous endoscopic lumbar interbody fusion (PE-LIF) and minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) for the treatment of lumbar spinal stenosis (LSS). Methods: We reviewed a total of 89 patients undergoing single-level surgery for lumbar spinal stenosis from January 2018 to July 2021. The cases were categorized as PE-LIF (Group PE-LIF, 41 cases) or MIS-TLIF (Group MIS-TLIF, 48 cases) approach. Parameters obtained at baseline through at least six months of follow-up were collected. The surgical outcomes involving the operative time, estimated blood loss, postoperative bed staying time, and length of hospital stays were analyzed. PROs included the Visual Analogue Scale (VAS), Oswestry Disability Index (ODI), modified MacNab standard evaluation, intervertebral fusion rate, and postoperative complications. Results A total of 89 patients were included in this analysis involving 41 patients who underwent PE-LIF and 48 patients who underwent MIS-TLIF. The 2 groups were similar in gender, age, body mass index, follow-up time and surgery levels (P > 0.05), and were not significantly different in the length of hospital stays (P > 0.05). PE-LIF had a significantly longer operative time, greater fluoroscopy time, lower estimated blood loss and shorter bed rest time than MIS-TLIF. Both groups improved significantly from baseline for the VAS and ODI scores. PE-LIF was associated with a lower VAS score for back pain at three-day after surgery. There were no significant differences between PE-LIF and MIS-TLIF in the excellent or good rates and intervertebral fusion rates at the last follow-up (P > 0.05). As for related complications, there were no significant complications occurred, and no significant differences were seen in the complications between both groups (P > 0.05). Conclusions: To summarize, PE-LIF and MIS-TLIF are both safe and effective for LSS. PE-LIF has a definite short-term curative effect with less trauma.